Effect of Storage on Fruitquality of Apricot (Prunus Armeniaca) - Drén, Gábor; Racskó, József; Thurzó, Sándor (Acta Agraria Debreceniensis, 2005)
The quality of a product is determined by numerous characteristics. As quality characteristics are polygenic, they cannot be improved easily. Moreover, there often is a negative correlation between the different parameters in the case of apricot. The firmness of fruits decreases with increasing size. The year effect also has a great influence on the expression of the potential quality of the given cultivar.Our examinations were carried out in 2004 at Boldogkőváralja, in the cold storage plant of the Northcot Ltd. We monitored the development of fruits from fructification until harvest, and also the quality changes during storage. 100 fruits were observed from each cultivar directly after harvest. We measured height, width, weight, firmness, dry matter content and seed weight. From each cultivar, 100 fruits were stored, of which 25 fruits were observed each week. The value and the dynamics of the changes in the parameters compared to the values at harvest varied greatly for the different cultivars. Strong correlations between the parameters have not been found within one cultivar either. The heavier fruits did not lose more weight, either in absolute value or relatively, than the lighter fruits. The increase in the firmness of fruits was not accompanied with a desirable decrease in the dry matter content.